Antibacterial studies of silver and gold nanoparticles loaded with selected drugs - Abdulkader, Hicham Masri (2020)
Infectious diseases possess a significant threat to human health, contributing to more than 17 million deaths, annually. The emergence of drug resistance combined with limited success in the discovery of new and effective antimicrobial therapeutics presents a substantial challenge to human and animal health. Nanotechnology may be used as an approach for effective drug development and delivery against infections caused by multi-drug resistant bacteria. In this study, selected groups of compounds, namely: antibiotics, central nervous system agents, quinazolinones, and flavonoid. Next, the various compounds were conjugated with gold and/or silver nanoparticles. Characterisation of drugs conjugated with nanoparticles were accomplished using UV-visible spectrophotometry, Atomic force microscopy, Fourier infrared transform spectroscopy, Dynamic light scattering, and Field emission scanning electron microscopy. The efficacy of drugs were evaluated against a selection of Gram positive and Gram-negative multi-drug resistant bacteria using bactericidal and bacteriostatic assays. Furthermore, the cytotoxicity of nanoconjugates on human cells were determined. Finally, the differential genetic expression of bacteria treated with silver nanoparticles and hesperidin-silver nanoparticles was carried out using RNA-seq, as this compound revealed potent bactericidal activity. Our results revealed that several drugs conjugated with nanoparticles exhibited potent bactericidal effects. These include: cephradine, quinzolinone, hesperidin, and naringen nanoconjugates which exhibited bactericidal effects against both methicillin resistant Staphylococcus aureus and neuropathogenic Escherichia coli K1. In addition, it was observed that pre-treatment of bacteria with several drug-nanoparticle conjugates inhibited bacterial-mediated host cell cytotoxicity. Interestingly, these drug-nanoparticle conjugates were non-toxic to primary human cells suggesting their selective toxicity to bacterial cells. Finally, differential genetic analysis of hesperidin- silver nanoparticles treated E. coli K1 revealed 122 genes (≥ 2-log fold change) that were differentially expressed (P<0.01), and significant regulation was observed for metabolic genes. To conclude, it is evident that conjugation of the selected drugs with gold and silver nanoparticles enhance their efficacy against bacteria in comparision to free drugs. Further research is needed to investigate the mechanism of action of these molecules and their in vivo efficacy, in order to develop much needed novel antimicrobials.